HPV vaccination among lesbian and bisexual women: Findings from a national survey of young adults - McRee, Annie-Laurie (2014)
BACKGROUND: Human papillomavirus (HPV) infection and associated cervical disease are common among all women, regardless of sexual identity, yet limited research has examined HPV vaccination among lesbian and bisexual women. METHODS: A national sample of lesbian and bisexual women ages 18-26 (n=543) completed our online survey during Fall 2013. We used multivariable logistic regression to identify correlates of HPV vaccine initiation (receipt of at least 1 dose) and completion (receipt of all 3 recommended doses among initiators). RESULTS: Overall, 45% of respondents had initiated HPV vaccine, and 70% of initiators reported completing the series. HPV vaccine initiation was higher among respondents who: were students, had received a healthcare provider's recommendation, perceived greater positive social vaccination norms, or anticipated greater regret if they did not get vaccinated and later got HPV. Initiation was lower among those who perceived greater HPV vaccine harms or greater barriers to getting the vaccine (all p<.05). HPV vaccine completion was higher among initiators who had a college degree while it was lower among those who perceived a greater likelihood of acquiring HPV or who anticipated greater regret if they got the vaccine and fainted (all p<.05). Among HPV vaccine initiators who had not yet completed the series, about half (47%) intended to get the remaining doses. CONCLUSIONS: Many lesbian and bisexual women are not getting vaccinated against HPV. Healthcare provider recommendations and women's health beliefs may be important leverage points for increasing vaccination among this population.